Copy number variation, increased gene expression, and molecular mechanisms of neurofascin in lung cancer - Samulin Erdem, Johanna (Mol Carcinog, 2017)
Metastasis and cell adhesion are key aspects of cancer progression. Neurofascin (NFASC) is a member of the immunoglobulin superfamily of adhesion molecules and, while studies on NFASC are inadequate, other members have been indicated pivotal roles in cancer progression and metastasis. This study aimed at increasing the knowledge on the involvement of adhesion molecules in lung cancer progression by studying the regulation and role of NFASC in non‐small cell lung cancer (NSCLC). Here, copy number variations in the NFASC gene were analyzed in tumor and non‐tumorous lung tissues of 204 NSCLC patients. Frequent gene amplifications (OR = 4.50, 95%CI: 2.27‐8.92, P ≤ 0.001) and increased expression of NFASC (P = 0.034) were identified in tumors of NSCLC patients. Furthermore, molecular mechanisms of NFASC in lung cancer progression were evaluated by investigating the effects of NFASC silencing on cell proliferation, viability, migration, and invasion using siRNA technology in four NSCLC cell lines. Silencing of NFASC did not affect cell proliferation or viability but rather decreased NSCLC cell migration (P ≤ 0.001) and led to morphological changes, rearrangements in the actin cytoskeleton and changes in F‐actin networks in migrating NSCLC cell lines. This study is the first to report frequent copy number gain and increased expression of NFASC in NSCLC. Moreover, these data suggest that NFASC is a novel regulator of NSCLC cell motility and support a role of NFASC in the regulation of NSCLC progression.